2000
DOI: 10.1016/s0735-1097(00)00650-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of dystrophin defects in adult male patients with dilated cardiomyopathy

Abstract: Although the overall prevalence of dystrophin defects in our consecutive DCM male series is low (6.5%), immunohistochemical and molecular studies are essential to identify protein and gene defects; screening studies are justified to define prevalence, clinical profile and genotype-phenotype correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 30 publications
2
47
0
1
Order By: Relevance
“…In addition, less severe mutations of dystrophin, such as missense mutations, may be associated with the sporadic form of DCM. 35 The clinical characteristics of DCM caused by dystrophin mutations have X-linked inheritance and are associated with increased CK concentrations, 29,32 as seen in the present study. Epidemiologic studies in Japan have reported that the male-to-female ratio is 2.6 for DCM, 1 which is comparable with the current finding demonstrating X-linked inheritance in several patients with dystrophin mutations.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, less severe mutations of dystrophin, such as missense mutations, may be associated with the sporadic form of DCM. 35 The clinical characteristics of DCM caused by dystrophin mutations have X-linked inheritance and are associated with increased CK concentrations, 29,32 as seen in the present study. Epidemiologic studies in Japan have reported that the male-to-female ratio is 2.6 for DCM, 1 which is comparable with the current finding demonstrating X-linked inheritance in several patients with dystrophin mutations.…”
Section: Discussionsupporting
confidence: 64%
“…28,29 In an earlier Japanese study, Shiga et al reported that no mutation of the muscle promoter/first exon region of the dystrophin gene was identified in 92 patients with DCM, 30 but they did not study the other regions of the gene. In contrast, we identified mutations in exons 45-52 in the dystrophin gene in 3 of 68 male patients (4.4%) with DCM in the present study, which suggests that analysis for mutations in exons 45-52 in the dystrophin gene may be more important in Japanese patients with DCM.…”
Section: Discussionmentioning
confidence: 99%
“…In this clinical cardiology setting, the only practical guide addressing to a possible mitochondrial origin of the cardiomyopathy is the endomyocardial biopsy, with ultrastructural and mitochondrial enzyme studies. EMB samples must be used to exclude the inflammatory or dystrophic 18 or autoimmune, etc. origin of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…28,30,31 Life expectancy is severely conditioned by the presence of the cardiomyopathy, closely related to the type of dystrophin gene mutation. 32,33 Heart transplantation is often required. 34 …”
Section: Duchenne Cardiomyopathymentioning
confidence: 99%
“…Mutations responsible for X-linked cardiomyopathy are confined into two regions of the dystrophin gene: i) mutations at the 5' end of the gene; 41 and ii) mutations in the spectrin-like dystrophin rod domain. 42 Mutations in NH2 domain seem to be associated to a more severe phenotype, 32 because patients with these mutations are unable to compensate the lack of M isoform in the heart, upregulating the B and P isoforms of dystrophin, as happens in the muscle.…”
Section: X-linked Dilated Cardiomyopathymentioning
confidence: 99%